1996
DOI: 10.1093/jat/20.6.492
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of N,N-Dimethyltryptamine and Harmala Alkaloids in Human Plasma after Oral Dosing with Ayahuasca

Abstract: Harmine, harmaline, tetrahydroharmine (THH), and N,N-dimethyltryptamine (DMT) were quantitated in plasma from 15 healthy male volunteers after the ingestion of ayahuasca, a beverage that has been used for religious purposes in Brazil since pre-Columbian times. A growing awareness of the interest in this ancient shamanistic practice in modern urban cultures and the widespread popular dissemination of the inebriant effects and type and sources of the plant admixtures used to prepare the beverage have provided ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
14

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 12 publications
3
97
0
14
Order By: Relevance
“…The synthesis of tetrahydroharmine was performed according to the procedure described by Callaway et al (1996). In summary, harmaline hydrochloride (251 mg, 1.0 mmol) was slowly added to a methanolic sodium borohydride solution (38 mg, 1.0 mmol) at 0°C.…”
Section: Synthesis Of Tetrahydroharminementioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of tetrahydroharmine was performed according to the procedure described by Callaway et al (1996). In summary, harmaline hydrochloride (251 mg, 1.0 mmol) was slowly added to a methanolic sodium borohydride solution (38 mg, 1.0 mmol) at 0°C.…”
Section: Synthesis Of Tetrahydroharminementioning
confidence: 99%
“…Peruvian ayahuasca (100 mL) has been shown to contain dimethyltryptamine (60 mg), harmine (467 mg), harmaline (41 mg) and tetrahydroharmine (160 mg) using two-dimensional thin-layer chromatography, high-performance liquid chromatography and gas chromatography-mass spectrometry (McKenna et al, 1984), whereas Brazilian ayahuasca (100 mL) has been shown to contain 24, 170, 20 and 107 mg respectively of the same four alkaloids using gas chromatography and high-performance liquid chromatography (Callaway et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The freeze-dried homogenized material had been obtained from a 9.6-liter batch of ayahuasca. The DMT content in the lyophilizate had been determined by HPLC, as described by Callaway et al [19], and the ß-carboline constituents were determined following a modification of the method described in that study. The 9.6-liter batch yielded 611 g of freeze-dried powder, containing 8.33 mg of DMT, 14.13 mg of harmine, 0.96 mg of harmaline and 11.36 mg of tetrahydroharmine per gram.…”
Section: Drugmentioning
confidence: 99%
“…La méthode de dosage de Callaway appliquée à 15 volontaires ayant consommé de l'ayahuasca (2 ml/kg contenant harmine 1,7 mg/ml, harmaline 0,2 mg/ml, tétrahydroharmine 1,1 mg/ml et DMT 0,25 mg/ml) au cours d'un rite religieux, a permis de mesurer les concentrations sériques moyennes suivantes : harmine 114,6 ng/ml, harmaline 6,2 ng/ml, tétrahydroharmine 90,8 ng/ml et DMT 15,8 ng/ml (8).…”
Section: Principes Actifs Relation Structure-activitéunclassified